Populasi dan Sebaran Jenis Moluska Dilindungi di Perairan Selat Lembeh, Kota Bitung, Sulawesi Utara - Ucu Yanu Arbi (Universitas Gadjah Mada, 2016)
Exploration of protected mollusks has been carried out at Lembeh Strait, Bitung, North Sulawesi for 30 months in 2007 until 2009. Protected mollusks can be found at Lembeh Strait and the population may decline because of environmental stress. The aim of this study is to determine populations of protected mollusc at Lembeh Strait waters. Observations were made at 15 locations with free collection methods. In this location, 175 individuals comprising 12 species of protected mollusks were collected. Tridacna maxima was the most extensive distribution in the research location. From the research, Lembeh Strait was advised to obtain marine protected areas.